The Use and Effectiveness of Powered Air Purifying Respirators in Health Care: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
Protecting 18 million United States health care workers from infectious agents - known and unknown - involves a range of occupational safety and health measures that include identifying and using appropriate protective equipment. The 2009 H1N1 influenza pandemic and the 2014 Ebola virus outbreak in West Africa have called raised questions about how best to ensure appropriate and effective use of different kinds of personal protective equipment such as respirators, not only to promote occupational safety but also to reduce disease transmission. The Use and Effectiveness of Powered Air Purifying Respirators in Health Care is the summary of a workshop convened by the Institute of Medicine Standing Committee on Personal Protective Equipment for Workplace Safety and Health to explore the current state of practices and research related to powered air purifying respirator (PAPRs) and potential updates to performance requirements. Presentations and discussions highlighted current health care practices using PAPRs and outlined the research to date on the use and effectiveness of PAPRs in health care settings with a focus on the performance requirements. The Use and Effectiveness of Powered Air Purifying Respirators in Health Care focuses on efficacy, current training, maintenance, supplies, and possible enhancements and barriers to use in inpatient, clinic, nursing home, and community (home) settings. This report also explores the strengths and weaknesses of using various approaches to health care PAPR standards.

Gain-of-Function Research: Summary of the Second Symposium, March 10-11, 2016 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
On March 10-11, 2016, the National Academies of Sciences, Engineering, and Medicine held a public symposium on potential U.S. government policies for the oversight of gain-of- function (GOF) research. This was the Academies' second meeting held at the request of the U.S. government to provide a mechanism to engage the life sciences community and the broader public and solicit feedback on optimal approaches to ensure effective federal oversight of GOF research as part of a broader U.S. government deliberative process. The first symposium, held in December 2014, examined the underlying scientific and technical questions surrounding the potential risks and benefits of GOF research involving pathogens with pandemic potential. The second symposium focused on discussion of the draft recommendations regarding GOF research of a Working Group of the National Science Advisory Board for Biosecurity. This report summarizes the key issues and ideas identified during the second symposium.

Crossing the Global Quality Chasm: Improving Health Care Worldwide - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
In 2015, building on the advances of the Millennium Development Goals, the United Nations adopted Sustainable Development Goals that include an explicit commitment to achieve universal health coverage by 2030. However, enormous gaps remain between what is achievable in human health and where global health stands today, and progress has been both incomplete and unevenly distributed. In order to meet this goal, a deliberate and comprehensive effort is needed to improve the quality of health care services globally. Crossing the Global Quality Chasm: Improving Health Care Worldwide focuses on one particular shortfall in health care affecting global populations: defects in the quality of care. This study reviews the available evidence on the quality of care worldwide and makes recommendations to improve health care quality globally while expanding access to preventive and therapeutic services, with a focus in low-resource areas. Crossing the Global Quality Chasm emphasizes the organization and delivery of safe and effective care at the patient\/provider interface. This study explores issues of access to services and commodities, effectiveness, safety, efficiency, and equity. Focusing on front line service delivery that can directly impact health outcomes for individuals and populations, this book will be an essential guide for key stakeholders, governments, donors, health systems, and others involved in health care.

International Infectious Disease Emergencies and Domestic Implications for the Public Health and Health Care Sectors: Workshop in Brief - Institute of Medicine (The National Academies Press, 2015)
Emerging infectious disease events present a threat to U.S. national security, and we need improved efforts to coordinate a response both domestically and with global partners. The most recent outbreak of the Ebola virus disease in West Africa is the largest to date, affecting multiple countries simultaneously and once again bringing the challenges of global health security to the forefront of international preparedness discussions. The outbreak in the United States exposed health care system gaps and brought to a head the need for increased communication between hospitals and health departments and the need for clearer direction and coordination from state and federal agencies on operational standards and practices. This Workshop in Brief summarizes a session held by the Institute of Medicine's (IOM's) Forum on Medical and Public Health Preparedness for Catastrophic Events at the 2015 Preparedness Summit to discuss international public health emergencies, such as Ebola, and their corresponding impact on state and local public health and health care systems.

Building Communication Capacity to Counter Infectious Disease Threats: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Building communication capacity is a critical piece of preparing for, detecting, and responding to infectious disease threats. The International Health Regulations (IHR) establish risk communication2014the real-time exchange of information, advice, and opinions between experts or officials and people who face a threat to their survival, health, and economic or social well-being2014as a core capacity that World Health Organization member states must fulfill to strengthen the fight against these threats. Despite global recognition of the importance of complying with IHR, 67 percent of signatory countries report themselves as not compliant. By investing in communication capacity, public health and government officials and civil society organizations facing health crises would be prepared to provide advice, information, and reassurance to the public as well as to rapidly develop messages and community engagement activities that are coordinated and take into account social and behavioral dynamics among all sectors. To learn about current national and international efforts to develop the capacity to communicate effectively during times of infectious disease outbreaks, and to explore gaps in the research agenda that may help address communication needs to advance the field, the Forum on Microbial Threats of the National Academies of Sciences, Engineering, and Medicine convened a 1.5 day workshop on December 13 and 14, 2016, in Washington, DC. Participants reviewed progress and needs in strengthening communication capacity for dealing with infectious disease threats for both outbreaks and routine challenges in the United States and abroad. This publication summarizes the presentations and discussions from the workshop.

Integrating Clinical Research into Epidemic Response: The Ebola Experience - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
The 201420132015 Ebola epidemic in western Africa was the longest and most deadly Ebola epidemic in history, resulting in 28,616 cases and 11,310 deaths in Guinea, Liberia, and Sierra Leone. The Ebola virus has been known since 1976, when two separate outbreaks were identified in the Democratic Republic of Congo (then Zaire) and South Sudan (then Sudan). However, because all Ebola outbreaks prior to that in West Africa in 201420132015 were relatively isolated and of short duration, little was known about how to best manage patients to improve survival, and there were no approved therapeutics or vaccines. When the World Heath Organization declared the 2014-2015 epidemic a public health emergency of international concern in August 2014, several teams began conducting formal clinical trials in the Ebola affected countries during the outbreak. Integrating Clinical Research into Epidemic Response: The Ebola Experience assesses the value of the clinical trials held during the 201420132015 epidemic and makes recommendations about how the conduct of trials could be improved in the context of a future international emerging or re-emerging infectious disease events.

Global Health Risk Framework: Governance for Global Health: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Since the 2014 Ebola outbreak many public- and private-sector leaders have seen a need for improved management of global public health emergencies. The effects of the Ebola epidemic go well beyond the three hardest-hit countries and beyond the health sector. Education, child protection, commerce, transportation, and human rights have all suffered. The consequences and lethality of Ebola have increased interest in coordinated global response to infectious threats, many of which could disrupt global health and commerce far more than the recent outbreak. In order to explore the potential for improving international management and response to outbreaks the National Academy of Medicine agreed to manage an international, independent, evidence-based, authoritative, multistakeholder expert commission. As part of this effort, the Institute of Medicine convened four workshops in summer of 2015 to inform the commission report. The presentations and discussions from the Governance for Global Health Workshop are summarized in this report.

Emerging Viral Diseases: The One Health Connection: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
In the past half century, deadly disease outbreaks caused by novel viruses of animal origin - Nipah virus in Malaysia, Hendra virus in Australia, Hantavirus in the United States, Ebola virus in Africa, along with HIV (human immunodeficiency virus), several influenza subtypes, and the SARS (sudden acute respiratory syndrome) and MERS (Middle East respiratory syndrome) coronaviruses - have underscored the urgency of understanding factors influencing viral disease emergence and spread. Emerging Viral Diseases is the summary of a public workshop hosted in March 2014 to examine factors driving the appearance, establishment, and spread of emerging, re-emerging and novel viral diseases; the global health and economic impacts of recently emerging and novel viral diseases in humans; and the scientific and policy approaches to improving domestic and international capacity to detect and respond to global outbreaks of infectious disease. This report is a record of the presentations and discussion of the event.

Regional Disaster Response Coordination to Support Health Outcomes: Summary of a Workshop Series - Institute of Medicine (The National Academies Press, 2015)
When disaster strikes, it rarely impacts just one jurisdiction. Many catastrophic disaster plans include support from neighboring jurisdictions that likely will not be available in a regional disaster. Bringing multiple stakeholders together from sectors that do not routinely work with each other can augment a response to a disaster, but can also be extremely difficult because of the multi-disciplinary communication and coordination needed to ensure effective medical and public health response. As many communities within a region will have similar vulnerabilities, a logical step in planning is to establish responsibilities and capacities, and be able to work toward common goals to address all-hazards when the entire region is affected. To explore these considerations, the Institute of Medicine's Forum on Medical and Public Health Preparedness for Catastrophic Events organized a series of three regional workshops in 2014 to explore opportunities to strengthen the regional coordination required in response to a large scale multijurisdictional disaster. The purpose of each regional workshop was to discuss ways to strengthen coordination among multiple jurisdictions in various regions to ensure fair and equitable treatment of communities from all impacted areas. Regional Disaster Response Coordination to Support Health Outcomes summarizes the presentation and discussion of these workshops.

Global Health Impacts of Vector-Borne Diseases: Workshop Summary - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Pathogens transmitted among humans, animals, or plants by insects and arthropod vectors have been responsible for significant morbidity and mortality throughout recorded history. Such vector-borne diseases 2013 including malaria, dengue, yellow fever, and plague 2013 together accounted for more human disease and death in the 17th through early 20th centuries than all other causes combined. Over the past three decades, previously controlled vector-borne diseases have resurged or reemerged in new geographic locations, and several newly identified pathogens and vectors have triggered disease outbreaks in plants and animals, including humans. Domestic and international capabilities to detect, identify, and effectively respond to vector-borne diseases are limited. Few vaccines have been developed against vector-borne pathogens. At the same time, drug resistance has developed in vector-borne pathogens while their vectors are increasingly resistant to insecticide controls. Furthermore, the ranks of scientists trained to conduct research in key fields including medical entomology, vector ecology, and tropical medicine have dwindled, threatening prospects for addressing vector-borne diseases now and in the future. In June 2007, as these circumstances became alarmingly apparent, the Forum on Microbial Threats hosted a workshop to explore the dynamic relationships among host, pathogen(s), vector(s), and ecosystems that characterize vector-borne diseases. Revisiting this topic in September 2014, the Forum organized a workshop to examine trends and patterns in the incidence and prevalence of vector-borne diseases in an increasingly interconnected and ecologically disturbed world, as well as recent developments to meet these dynamic threats. Participants examined the emergence and global movement of vector-borne diseases, research priorities for understanding their biology and ecology, and global preparedness for and progress toward their prevention, control, and mitigation. This report summarizes the presentations and discussions from the workshop.

Exploring Lessons Learned from a Century of Outbreaks: Readiness for 2030: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
In November 2018, an ad hoc planning committee at the National Academies of Sciences, Engineering, and Medicine planned two sister workshops held in Washington, DC, to examine the lessons from influenza pandemics and other major outbreaks, understand the extent to which the lessons have been learned, and discuss how they could be applied further to ensure that countries are sufficiently ready for future pandemics. This publication summarizes the presentations and discussions from both workshops.

Vector-Borne Diseases: Understanding the Environmental, Human Health, and Ecological Connections: Workshop Summary - Institute of Medicine (The National Academies Press, 2008)
Vector-borne infectious diseases, such as malaria, dengue fever, yellow fever, and plague, cause a significant fraction of the global infectious disease burden; indeed, nearly half of the world's population is infected with at least one type of vector-borne pathogen (CIESIN, 2007; WHO, 2004a). Vector-borne plant and animal diseases, including several newly recognized pathogens, reduce agricultural productivity and disrupt ecosystems throughout the world. These diseases profoundly restrict socioeconomic status and development in countries with the highest rates of infection, many of which are located in the tropics and subtropics. Although this workshop summary provides an account of the individual presentations, it also reflects an important aspect of the Forum philosophy. The workshop functions as a dialogue among representatives from different sectors and allows them to present their beliefs about which areas may merit further attention. These proceedings summarize only the statements of participants in the workshop and are not intended to be an exhaustive exploration of the subject matter or a representation of consensus evaluation. Vector-Borne Diseases : Understanding the Environmental, Human Health, and Ecological Connections, Workshop Summary (Forum on Microbial Threats) summarizes this workshop.

The Global Crisis of Drug-Resistant Tuberculosis and Leadership of China and the BRICS: Challenges and Opportunities: Summary of a Joint Workshop by the Institute of Medicine and the Institute of Microbiology, Chinese Academy of Sciences - Institute of Medicine (The National Academies Press, 2014)
Multidrug-resistant tuberculosis (TB) is caused by bacteria resistant to isoniazid and rifampicin, the two most effective first-line anti-TB drugs, originally developed and introduced in the 1950 and 1960s. Since 2008, the Forum on Drug Discovery, Development, and Translation of the Institute of Medicine has hosted or co-hosted six domestic and international workshops addressing the global crisis of drug-resistant TB, with special attention to the BRICS countries - Brazil, Russia, India, China, and South Africa. The Global Crisis of Drug-Resistant Tuberculosis and Leadership of China and the BRICS is the summary of a workshop convened to address the current status of drug-resistant TB globally and in China. This report considers lessons learned from high burden countries; highlights global challenges to controlling the spread of drug-resistant strains; and discusses innovative strategies to advance and harmonize local and international efforts to prevent and treat drug-resistant TB. Additionally, the report examines the problem of MDR TB and emergent TB strains that are potentially untreatable with drugs available and considers the critical leadership role of the BRICS countries in addressing the threats and opportunities in drug-resistant TB.

Infectious Disease Movement in a Borderless World: Workshop Summary - Institute of Medicine
Modern transportation allows people, animals, and plants–and the pathogens they carry–to travel more easily than ever before. The ease and speed of travel, tourism, and international trade connect once-remote areas with one another, eliminating many of the geographic and cultural barriers that once limited the spread of disease. Because of our global interconnectedness through transportation, tourism and trade, infectious diseases emerge more frequently; spread greater distances; pass more easily between humans and animals; and evolve into new and more virulent strains. The IOM's Forum on Microbial Threats hosted the workshop \

Understanding the Economics of Microbial Threats: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Microbial threats, including endemic and emerging infectious diseases and antimicrobial resistance, can cause not only substantial health consequences but also enormous disruption to economic activity worldwide. While scientific advances have undoubtedly strengthened our ability to respond to and mitigate the mortality of infectious disease threats, events over the past two decades have illustrated our continued vulnerability to economic consequences from these threats. To assess the current understanding of the interaction of infectious disease threats with economic activity and suggest potential new areas of research, the National Academies of Sciences, Engineering, and Medicine planned a 1.5-day public workshop on understanding the economics of microbial threats. This workshop built on prior work of the Forum on Microbial Threats and aimed to help transform current knowledge into immediate action. This publication summarizes the presentations and discussions from the workshop.

Sustaining Global Surveillance and Response to Emerging Zoonotic Diseases - Institute of Medicine; National Research Council
H1N1 (\

Global Health and the Future Role of the United States - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
While much progress has been made on achieving the Millenium Development Goals over the last decade, the number and complexity of global health challenges has persisted. Growing forces for globalization have increased the interconnectedness of the world and our interdependency on other countries, economies, and cultures. Monumental growth in international travel and trade have brought improved access to goods and services for many, but also carry ongoing and ever-present threats of zoonotic spillover and infectious disease outbreaks that threaten all. Global Health and the Future Role of the United States identifies global health priorities in light of current and emerging world threats. This report assesses the current global health landscape and how challenges, actions, and players have evolved over the last decade across a wide range of issues, and provides recommendations on how to increase responsiveness, coordination, and efficiency 2013 both within the U.S. government and across the global health field.

The Neglected Dimension of Global Security: A Framework to Counter Infectious Disease Crises (The National Academies Press, 2016)
Since the 2014 Ebola outbreak many public- and private-sector leaders have seen a need for improved management of global public health emergencies. The effects of the Ebola epidemic go well beyond the three hardest-hit countries and beyond the health sector. Education, child protection, commerce, transportation, and human rights have all suffered. The consequences and lethality of Ebola have increased interest in coordinated global response to infectious threats, many of which could disrupt global health and commerce far more than the recent outbreak. In order to explore the potential for improving international management and response to outbreaks the National Academy of Medicine agreed to manage an international, independent, evidence-based, authoritative, multistakeholder expert commission. As part of this effort, the Institute of Medicine convened four workshops in summer of 2015. This commission report considers the evidence supplied by these workshops and offers conclusions and actionable recommendations to guide policy makers, international funders, civil society organizations, and the private sector.

Global Health Risk Framework: Research and Development of Medical Products: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Since the 2014 Ebola outbreak many public- and private-sector leaders have seen a need for improved management of global public health emergencies. The effects of the Ebola epidemic go well beyond the three hardest-hit countries and beyond the health sector. Education, child protection, commerce, transportation, and human rights have all suffered. The consequences and lethality of Ebola have increased interest in coordinated global response to infectious threats, many of which could disrupt global health and commerce far more than the recent outbreak. In order to explore the potential for improving international management and response to outbreaks the National Academy of Medicine agreed to manage an international, independent, evidence-based, authoritative, multistakeholder expert commission. As part of this effort, the Institute of Medicine convened four workshops in summer of 2015 to inform the commission report. The presentations and discussions from the Workshop on Research and Development of Medical Products are summarized in this report.

Supporting Family and Community Investments in Young Children Globally: Summary of a Joint Workshop by the National Academies of Sciences, Engineering, and Medicine and the Ethiopian Academy of Sciences - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
To examine the science, policy, and practice surrounding supporting family and community investments in young children globally and children in acute disruptions, the National Academies of Sciences, Engineering, and Medicine held a workshop in partnership with the Ethiopian Academy of Sciences in Addis Ababa, Ethiopia, from July 27-29, 2015. The workshop examined topics related to supporting family and community investments in young children globally. Examples of types of investments included financial and human capital. Participants also discussed how systems can better support children, families, and communities through acute disruptions such as the Ebola outbreak. Over the course of the 3-day workshop, researchers, policy makers, program practitioners, funders, young influencers, and other experts from 19 countries discussed how best to support family and community investments across areas of health, education, nutrition, social protection, and other service domains. This report summarizes the presentations and discussions from the workshop.